A public–private partnership to enrich the development of in silico predictive models for pharmacokinetic and cardiotoxic properties. Issue 5 (May 2021) - Komura, Hiroshi; Watanabe, Reiko; Kawashima, Hitoshi; Ohashi, Rikiya; Kuroda, Masataka; Sato, Tomohiro; Honma, Teruki; Mizuguchi, Kenji
Highlights: A framework for a public-private (PP) partnership was established in Japan. This PP partnership consortium was constructed by private and public sectors. Pharmacokinetic/cardiotoxic small molecule drug databases were developed. These databases allowed us to build robust in silico prediction models. Abstract : A novel framework for a public–private (PP) partnership was established by a national initiative of the Development of a Drug Discovery Informatics System, supported by the Japan Agency for Medical Research and Development (AMED). This informatics PP partnership consortium comprised private and public sectors. A database of pharmacokinetic (PK) and cardiotoxic properties was developed, with considerable expansion after integrating proprietary data from private-sector members. This database led to robust in silico prediction models with higher performance than those from the original database. This partnership is a unique example worldwide and could substantially strengthen drug discovery capabilities in both sectors.